(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Films are the rich tool of communicating ideologies to people ever since it was evolved. Each film maker has their own strategy and style in knotting up their story to the audience and it is up to the audience to perceive the essence of the portrayal. Usage of signs and codes creates the magic while reception of these content by the audience in the intended way. The recent International release of Karthik Subburaj is the film titled “Mercury.” It is a movie often misinterpreted to be silent film but actually it is not. As a part of the movie is silent, signs and codes are used to convey message and meaning in the film. This aspect of this thriller movie and the different colour tone used, and the characterization of the affected people in the industry that includes Prabhu Deva, and their performance has lead to this study on the semiotic approach of this film. The aim of this study is to decode the denotations and connotations in the film and verify the effective usage of signs and codes used by the director of the film. How to cite this article: Prabhakar SM. A Study on the Semiotic Approach used in the Kollywood Film ‘Mercury’. J Adv Res Jour Mass Comm 2018; 5(4): 45-49. DOI: https://doi.org/10.24321/2395.3810.201818